Identificacao de sintomas e queixas psiquiatricas no primeiro atendimento clinico de um hospital universitario - Smaira, Sumaia Inaty; Torres, Albina Rodrigues; Cacace, Luciana Avesani; Giovanetti, Frederico Atra; Kerr-Corrêa, Florence [UNESP] (My University, 1997)
A prevalence study was performed of psychiatric problems among patients of first attendance in Clinical Hospital of Medicine Faculty of Botucatu - UNESP. It was analysed 704 attendance cards. 13.5% of these comprised antecedent complaints or a psychiatric diagnosis. The psychiatric cases, although frequent, were subdiagnosed by clinicians and not much conducted for specialized treatment (42%). The depression was the psychiatric disturbance less identified by general clinicians (null case). The alcoholism was diagnosed in 23.2% of cases, that only received clinical leading: solely 7.4% of diagnosed cases were guided for psychiatric treatment. The data emphasized the necessity of best preparation of medicine's students for to recognize, treat and/or conduct the more prevalent psychiatric disturbances, as recommended by CINAEM (Comissao Interestadual Nacional de Avaliacao do Ensino Medico) and that are, in our case, anxiety, depressive/dysthymic troubles and alcoholism.
Identification of symptoms and psychiatric complaints in the first clinical attendance of a university hospital